(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article is dedicated to the etymological survey of several Uzbek lacunas denoting objects, concepts and situations that do not exist in the practical experience of people who speak a different language and their importance in the Uzbek language as a primary source and type of linguocultureme. Furthermore, the material presents non-equivalent lexis, words reflected nation’s culture in themselves with their massive linguoculturulogical vitality as they are national wealth of Uzbek tradition. The main aim of the article is to enrich and contribute to the study of linguoculturology as the new field of linguistics.